Prevalence of Histologically Proven Acute Appendicitis And Incidental Carcinoid Tumour in the Practice of Surgical Pathology at BPKIHS - Upadhyaya, P; Agarwal, C S; Karak, A K; Karki, S; Pradhan, A; Subba, T N (Health Renaissance, 2016)
Background: Appendicitis is the most common cause of acute abdominal pain requiring surgical intervention. Objective: To determine the relative prevalence of histologically proven acute appendicitis in surgically respected specimens with clinical diagnosis of acute appendicitis and also to find out the rate of occurrence of characinoid tumour as an incidental histologic finding. Methods: It is a retrospective study involving all gross specimens received in the department of pathology over a period of twenty months (1.1.2006 to 31.8.2007). Histologic data on 515 appendicectomy samples (clinically diagnosed as appendicitis) of the total 7295 specimens received over a period of twenty months were retrieved from the archives of department of pathology, with exclusion of appendectomy incidental to another surgical procedure. Results: Appendectomy specimens constituted 7.0% (n=515; M:F 1.1:1) of all surgical pathologic specimens (n=7295) at B.P.K.I.H.S. The breakups of histologic diagnoses are: acute appendicitis with or without periappendicitis and gangrenous change (93.6%, n=482), “receding appendicitis” (5.4%, n=28), and normal histology (1.0%, n= 5). Carcinoid tumours were detected incidentally in three cases (0.58%) out of all appendectomy specimens. Conclusion: Analysis of data revealed a prevalence of 6.99% of histologically proven acute appendicitis in this tertiary health care set up. The rate of occurrence of carcinoid tumour was 0.58%. Health Renaissance 2014;12(3): 197-203